2010
DOI: 10.1542/peds.2009-1046
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Magnetic Resonance Biomarkers in Neonatal Encephalopathy: A Meta-analysis

Abstract: Deep gray matter Lac/NAA is the most accurate quantitative MR biomarker within the neonatal period for prediction of neurodevelopmental outcome after NE. Lac/NAA may be useful in early clinical management decisions and counseling parents and as a surrogate end point in clinical trials that evaluate novel neuroprotective therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
262
3
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 326 publications
(283 citation statements)
references
References 69 publications
14
262
3
4
Order By: Relevance
“…With CBMRI brain lesions developed in infants with HIE can be determined at an early time (14). Therefore, imaging is recommended on the 2-8 th days (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…With CBMRI brain lesions developed in infants with HIE can be determined at an early time (14). Therefore, imaging is recommended on the 2-8 th days (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…la ecografía cerebral juega un importante rol en los primeros días de vida, especialmente durante períodos inestables y/o de hipotermia, entregando información, en la misma cuna del enfermo, sobre hemorragias, lesiones de nú-cleos basales y con doppler cerebral evidenciar signos de vasodilatación cerebral y/o perdida de la regulación del flujo cerebral.modalidad 36 . la espectroscopia por resonancia magnética (MRs) es el predictor más sensible de resultado en los neonatos con encefalopatía, por lo tanto se debe considerar adicionar a RNM, si ello es posible 37 .…”
Section: Neuroimágenesunclassified
“…Thayyil et al 10 used recently developed Cochrane methodology for performing systematic reviews of diagnostic tests. They carefully reviewed studies that related MR findings in infants with HIE to neurodevelopmental outcome at 12 months or later.…”
Section: Meta-analysismentioning
confidence: 99%
“…Thayyil et al 10 identified 32 studies that included a total of 860 newborn infants with HIE. Their detailed analysis revealed MR spectroscopy to be more specific and sensitive for predicting neurodevelopmental impairment than conventional imaging.…”
Section: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation